Carboxylesterase activities as potential biomarkers of pollution in marine pelagic predators - David Nos (Elsevier, 2021)
Assessment of chemical exposures in the marine environment is frequently undertaken in sedentary organisms inhabiting coastal environments. However, predatory pelagic fish should be considered sentinel species, as they play an important role in the sustainability of the ecosystems due to their high position in trophic webs. In this study, carboxylesterase (CE) activities were analysed in four predatory tuna species of commercial interest along the western Mediterranean Sea: little tunny (Euthynnus alletteratus), Atlantic bonito (Sarda sarda), bullet tuna (Auxis rochei) and albacore tuna (Thunnus alalunga). CEs are potential biomarkers of chemical exposure, as they are an important family of enzymes involved in the metabolism of xenobiotic and endogenous compounds. CE measures were taken from the liver of these tuna species using five commercial substrates: 4-nitrophenyl acetate (4NPA), 4-nitrophenyl butyrate (4NPB), 1-naphthyl acetate (1NA), 1-naphthyl butyrate (1NB), and 2-naphthyl acetate (2NA). Butyrate substrates (1NB and 4NPB) yielded the highest hydrolysis rates, and were thus the best substrates for these measures. CE activities differed between species. The larger differences were attained with 1NB-CE, with higher activities seen in bullet tuna, followed by little tunny, Atlantic bonito and albacore tuna. Individual size was identified as one of the main factors modulating CE activities, while there was no evidence for a role for trophic level (measured as δ15N). Using little tunny as sentinel, no geographical differences but inter-annual variation in CE activity was observed. The kinetic parameters and in vitro exposure to the pesticide dichlorvos provided complementary information on the sensitivity of tuna CEs to this model pesticide. Our results propose that the little tunny could be considered a potential bioindicator species in the pelagic realm.